Two sequential layers of antibody‐mediated control of Legionella pneumophila infection. Issue 9 (18th June 2019) - Weber, Stefan S.; Stoycheva, Diana; Nimmerjahn, Falk; Oxenius, Annette
Abstract: Protective immunity against intracellular pathogens, including bacteria, usually relies on cellular immunity. However, antibodies are also implicated in mediating protection against intracellular bacteria. In case of airway infection with Legionella pneumophila (Lpn), the causative agent of Legionnaires' disease, pre‐existing Lpn ‐specific antibodies were shown to afford protection within two days of infection. Here we dissected the early kinetics of Ab‐mediated protection against airway Lpn infection and observed two kinetically and mechanistically distinct phases of protection by passively administered antibodies. Within the first hour of infection, Lpn ‐opsonizing antibodies provided almost 10‐fold protection in an antibody Fc‐dependent, but FcR‐independent manner. Later on, by two days post infection, Lpn ‐specific Ab‐mediated protection strictly involved FcγR, Syk kinase activity in alveolar macrophages and induction of reactive oxygen species (ROS). The findings presented here contribute to the understanding of the mechanisms of Ab‐mediated control of Lpn infection in actively or passively immunized individuals. Abstract : Legionella pneumophila ‐specific antibodies exert a biphasic protective function. Immediate protection (i.e. within one hour post infection) relies on the Fc part of IgG, but not on activating Fcγ receptors, while later protection (2 days p.i.) depends on activating Fcγ receptors and downstream Nox‐2‐dependent ROS production in alveolar macrophages.